Pulter's end: mortality, mortalism, and the poetics of doubt and certitude - Graham, Kenneth J. E. (Literature and theology, 2025)
Hester Pulter's views of the death, decay, and dissolution of bodies, as well as of their eventual reconstitution, "involution," and resurrection, are eclectic and at times idiosyncratic. In demonstrating and exploring these views, her poems display both conviction and skepticism, driven not only by a need for emotional comfort in the face of looming death, but also by curiosity in response to the mystery it poses. By changing the forms of her poems, Pulter combines reassurance and inquiry in a variety of ways, sometimes emphasizing one, sometimes the other. How these poems believe - with firm conviction, epistemological openness, or some combination of the two - is a product of how they are written.